Delayed Tension Pneumocephalus following Gunshot Wound to the Head: A Case Report and Review of the Literature - Arthur Wang; Elena Solli; Nathan Carberry; Virany Hillard; Adesh Tandon (Case Reports in Surgery)
Tension pneumocephalus is a rare complication of head trauma and neurosurgical procedures, amongst other causes. It is defined by the combination of intracranial air, increased intracranial pressure, and mass effect. Although it often presents soon after surgery, it can also rarely present in a delayed fashion. We present a case of delayed tension pneumocephalus, occurring approximately 16 weeks after bifrontal craniectomy for a self-inflicted gunshot wound. Following a month of rhinorrhea, postnasal drip, and cough, the patient presented with a sensation of expansion in the area of the right forehead. As tension pneumocephalus is an emergency that can be fatal, this patient was treated expediently and avoided severe neurological deficits. The case recounted here is important as a demonstrative example that tension pneumocephalus does not always follow a defined course immediately after trauma or neurosurgery but rather can develop insidiously without obvious signs.